LIBRARY SERVICE SYSTEM IN POCKET (ONLINE BOOK RESERVATION) NORTH SUMATRA PROVINCIAL LIBRARY AND ARCHIVES OFFICE - Ika Wardani; Abdul Karim Batubara (STMIK Royal, 2023)
Abstrak: Through the library, the advancement of science and information technology also influences societal elements of life. The high level of community production makes it challenging for people to obtain library material needs, limiting engagement and library use. The Library and Archives Service of North Sumatra Province uses information and communication technology to meet user needs by developing technology-based services that facilitate effective and efficient library activities. Examples of these services include a library service system in a pocket (silapustaku) or online book reservations. To make it simpler to explain how the system functions and is utilized by the community, this study uses UML (Unified Modeling Language) modeling to examine the pocket library service system or online book reservation. A descriptive qualitative approach to the design of the UML system development is the research methodology adopted. The study's findings demonstrate a type of UML modeling design that enables each user to be viewed clearly and understood when utilizing the system. in order to build a library approach with the community and improve library performance via the use of technology. Keywords: Information System, Online Book Reservation, UML (Unified Modeling Language)Abstrak : Ilmu pengetahuan yang berkembang serta teknologi informasi yang berkermbang juga mempengaruhi aspek kehidupan di masyarakkat melalui perpustakaan. Perpustakaan dituntut untuk ikut berperan dalam meningkatkan kualitas layanannya dalam memenuhi kenutuhan informasi penggunanyal. dalam memenuhi kebutuhan pemustaka, Dinas Perpustakaan dan Arsip Provinsi Sumatera Utara memberikan inovasi pelayanan dengan pemanfaatan teknologi informasi dan komunikasi dengan menggunakan sistem layanan pustaka dalam saku (silapustaku) atau reservasi buku online sebagai pengembangan layanan berbasisi teknologi dalam proses memudahkan aktifitas perpustakaan yang efektif dan efesien. Penelitian ini bertujuan untuk menganalisis system layanan pustaka dalam saku atau reservasi buku online dengan menggunakan pemodelan UML (Unified Modeling Language) untuk memudahkan dalam memaparkan kerja system dan di gunakan oleh masyarakat. Metode penelitian yang di gunakan merupakan metode pendekatan kualitatif deskriptif dengan perancangan pengembangan system UML. Hasil kajian menunjukkan bentuk rancangan pemodelan menggunakan UML yang memungkinkan setiap pengguna dapat terlihat jelas dan mudah di mengerti dalam menggunakan system. Sehingga penggunaan teknologi mampu meningkatkan kinerja perpustakaan dan menjalin pendekatan perpustakaan dengan masyarakat. Kata Kunci: Sistem Informasi, Reservasi Buku Online, UML (Unified Modeling Language)